Nursing care experience in a grieving process - Luzmila Hernandez Sampayo (Universidad de Alicante, 2019)
Perinatal death from an institutional view is a matter of difficult confrontation for both, parents who experience the loss, as for the health personnel present at the event. Kristen Swanson theory considers that the goal of nursing is to provide care, for women and her family, significantly to help in the acceptance of the death of a loved one. The support health personnel provide for parents and their family, is significant in the acceptance of the loss and the development of the grieving process. This article tells the experience of a nurse in her interaction with a woman who faced the death of his daughter at the time of birth. It is analyzed based on the Kristen Swanson Care Theory, focuses on the meta-paradigmatics elements and processes or categories of care.